2015
DOI: 10.1126/science.aaa8035
|View full text |Cite
|
Sign up to set email alerts
|

Corticomotoneuronal cells are “functionally tuned”

Abstract: Corticomotoneuronal (CM) cells in the primary motor cortex (M1) have monosynaptic connections with motoneurons. They are one of the few sources of descending commands that directly influence motor output. We examined the contribution of CM cells to the generation of activity in their target muscles. The preferred direction of many CM cells differed from that of their target muscles. Some CM cells were selectively active when a muscle was used as an agonist. Others were selectively active when the same muscle w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
73
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 15 publications
4
73
0
Order By: Relevance
“…Task-dependent processing in M1 has also been observed in previous reaching and posture comparisons (Kurtzer et al 2005). While the latency between atypical and typical activity was much shorter than the latency between the muscular agonist and antagonist, a recent study by Griffin et al (2015) also showed that cells that were functionally tuned for antagonist activity show activity only shortly after those tuned for agonist activity. The antagonist activity was relatively weak in the present study because of the speed of reaching and the contribution of friction from the exoskeleton assisting the deceleration of the limb.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…Task-dependent processing in M1 has also been observed in previous reaching and posture comparisons (Kurtzer et al 2005). While the latency between atypical and typical activity was much shorter than the latency between the muscular agonist and antagonist, a recent study by Griffin et al (2015) also showed that cells that were functionally tuned for antagonist activity show activity only shortly after those tuned for agonist activity. The antagonist activity was relatively weak in the present study because of the speed of reaching and the contribution of friction from the exoskeleton assisting the deceleration of the limb.…”
Section: Discussionmentioning
confidence: 86%
“…It has been shown that neurons strongly active during precision grip were much less active for power grip that required more muscle force (Muir and Lemon 1983). As well, load representations can change between posture and movement, but their directional preference remains relatively constant (Kurtzer et al 2005) and can be only active when the muscle is used for a specific phase of movement (Griffin et al 2015). Even when neural activity reflects features such as the direction of the spatial goal, these neurons likely remain associated with a specific body part such as the wrist (Kakei et al 1999) or elbow/shoulder (Sergio and Kalaska 2003).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The direct access of New M1 to motoneurons enables it to bypass some spinal cord circuits and sculpt novel patterns of motor output, essential for highly skilled movements (Griffin, Hoffman, & Strick, 2015;Lemon, 2008). This result suggests that certain types of motor performance rely heavily on M1.…”
Section: Neuroanatomical Considerationsmentioning
confidence: 99%